Comparison of numerical, experimental and empirical results for flows over vertical drops. (1st January 2014) - Mansouri, R.; Ziaei, A.N.; Hinkelmann, R.
The complex flow over three vertical drops (horizontal apron, adverse apron, horizontal apron with an end sill) were studied numerically and compared to experiments and empirical functions. In addition to flow depth, energy loss, and free-surface profiles, detailed velocity, pressure and shear stress distribution, which are hard to be measured experimentally, were investigated. The 2D numerical results on a 57, 512-node grid, using standard k - ε turbulence model and standard wall function showed the best agreement with experimental results. The energy loss in the drop with an end sill was higher than the adverse apron drop and the latter more than the horizontal apron drop. The numerical length and velocity scales confirmed the experimental similarity profiles. However, due to dissipative nature of the turbulence model, the velocity gradient in the shear layer was numerically dispersed particularly near the pool end. The stagnation pressure and shear stress were computed numerically for the drops. The maximum stagnation pressure and shear stress occurred in the horizontal apron drop.